2023
DOI: 10.1007/s43762-023-00080-3
|View full text |Cite
|
Sign up to set email alerts
|

Urban modification of heavy rainfall: a model case study for Bhubaneswar urban region

Abstract: An increase in urbanization has been witnessed from 1980 to 2019 in Bhubaneswar, Odisha. The impact of this increase in urban areas on rainfall pattern and intensity has been assessed in this study. To evaluate these changes, four heavy rainfall events, such as 06th March 2017, 23rd May 2018, 20 – 22 July 2018, and 04 – 08 August 2018, have been simulated with 1980, 2000, and 2019 land use land cover (LULC) obtained from United States Geological Survey imageries. With these two LULC sensitivities, urban canopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…The close relationship between UHI, PBL heights and rainfall enhancement suggests that the thermodynamical effects are the main drivers for rainfall modification on the whole modeled timescale. Our results are in general agreement with several previous studies, which also highlighted the importance of thermodynamical effects of urban land-use on heavy rainfall in this region (Li et al 2017;Swain et al 2023).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The close relationship between UHI, PBL heights and rainfall enhancement suggests that the thermodynamical effects are the main drivers for rainfall modification on the whole modeled timescale. Our results are in general agreement with several previous studies, which also highlighted the importance of thermodynamical effects of urban land-use on heavy rainfall in this region (Li et al 2017;Swain et al 2023).…”
Section: Discussionsupporting
confidence: 93%
“…Lei et al (2008) accurately simulate the heavy rainfall rates of a particular storm case in Mumbai, and concluded about the important impact of urbanization on extremes. Swain et al (2023) recently showed that the urbanization could induce an intensification of rainfall in the Bhubaneshwar region, located in Northeastern India. Li et al (2017) also studied the projected impacts of LULC changes in the region, and found that an urbanization-increase scenario would lead to an increase in temperature and rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…And then our results demonstrate the trend and mean values of shorterduration heavy precipitation (≤3 days) frequency and amount from 1990 to 2021 in the LTB and RTB urban catchments are both larger than that in the RRB catchments (Eff >0). This corresponds well with other studies that have reported urbanization intensified daily or sub-daily heavy precipitation metrics at both regional and national scales (Lin et al, 2020;Mou et al, 2022;Pimonsree et al, 2022;Song et al, 2021;Swain et al, 2023;Yan et al, 2020;Z. Yao & Huang, 2023;Yuan et al, 2021;Zhu et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have documented that heavy precipitation is significantly intensified in urban areas compared to rural areas, supported by statistical and model-based evidence (Chang et al, 2021;Doan et al, 2022;J. Huang et al, 2022;Mou et al, 2022;Pimonsree et al, 2022;Song et al, 2021;Swain et al, 2023;Yan et al, 2020;Z. Yao & Huang, 2023;Zhu et al, 2019).…”
Section: Introductionmentioning
confidence: 86%
“…We build upon previous work by focusing on the regional scale meteorological impacts of heat mitigation technologies on a tropical urban environment (Khan, Akbari, et al., 2022). A majority of urban heat mitigation studies for the tropics have focused on the application of different strategies to improve the thermal balance of large and medium‐sized cities such as Singapore (Li & Norford, 2016; Mughal et al., 2019; Tan et al., 2015), Hong Kong (L. Chen & Ng, 2013; Cheng et al., 2010; Jim, 2015; Ng et al., 2012; Wong et al., 2013), Colombo (Emmanuel et al., 2007), Bhubaneswar (Swain et al., 2023), Mumbai (Dwivedi & Mohan, 2018), and Kolkata (Chatterjee et al., 2019). Despite the growing importance of urban climate mitigation research (Gonzalez et al., 2021; Khan, Akbari, et al., 2022; Krayenhoff et al., 2021), there exists a dearth of investigations focused on the impact of heat mitigation technologies on PBL dynamics in general and over tropical urban environments in particular.…”
Section: Introductionmentioning
confidence: 99%